REZEKNE CHILDREN MUSIC SCHOOL (1949-1956): ROUTINE OF AN EDUCATIONAL ESTABLISHMENT AND FUNCTIONS IN COMMUNICATION WITH SOCIETY - Caksa, Valda (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2016)
The goal of the article is, applying the interdisciplinary approach in the analysis of historical documents and stories about memories, to find out the most important features in the history of Children’s Musical School of Rezekne (1949-1956) managed by Jānis Ūsītis, describing also the personalities of the most important music teachers and composition of pupils.As the soviet ideology prohibited individuals from the role of a free social doer, believing it to be the an easily customizable for the needs of the reforms defined by the elite, the main attention in the article is paid to the everyday life of school staff and its functions in communication with society. The article is methodologically based on the historical analysis of discourse.